Effect of Dietary Vegetable Oil Supplementation on C18 Fatty Acids and Conjugated Linoleic Acid Production; An In vitro Fermentation Study - Panatuk, Julakorn; Uriyapongson, Suthipong; Nawanukraw, Chainarong; Phoemchalard, Chirasak; Pornanake, Pitukpol (Pakistan Journal of Nutrition, 2013)
An in vitro rumen fermentation trial was conducted to investigate effect of dietary vegetable oil supplement on fatty acids metabolism in cattle. The incubation was carried out using rumen fluid obtained from Brahman x Native crossbred beef cattle. The diets were formulated by using basal diet with no vegetable oil (CON), basal diet with 4% of palm oil (PO), 4% of canola oil (CA), 4% of coconut oil (CO) and 4% of sunflower oil (SF). Fatty acid profiles were determined at 12, 24 and 48 h after incubation time. The results found that linoleic acid (LA) was decreased with diet CON, diet PO, diet CA and diet SF (p